1962
DOI: 10.1111/j.1476-5381.1962.tb01157.x
|View full text |Cite
|
Sign up to set email alerts
|

Depletion and Replacement of the Adrenaline and Noradrenaline Contents of the Rat Adrenal Gland, Following Treatment With Reserpine

Abstract: The effect of reserpine on the adrenaline and noradrenaline contents of rat adrenal glands has been studied. Given subcutaneously to male albino Wistar rats in 3 daily doses of 1 mg/kg, it caused, 24 hr after the final dose, a similar percentage loss of adrenaline and noradrenaline of approximately 50%. Subsequently the adrenaline content slowly increased, until at 14 days from the begining of the experiment there was no significant difference between the reserpine-treated and the control glands. In contrast, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

1964
1964
1995
1995

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 17 publications
0
10
0
Order By: Relevance
“…The adrenaline content of the adrenal gland is only moderately depleted by the doses of reserpine here employed (Callingham & Mann, 1962); therefore there is no functional inactivation of the adrenal medulla. Indeed, reserpine causes an increased adrenaline excretion which is reduced by the administration of mecamylamine.…”
Section: Action Of Reserpine and Dexamphetamine On The Urinary Catechmentioning
confidence: 74%
“…The adrenaline content of the adrenal gland is only moderately depleted by the doses of reserpine here employed (Callingham & Mann, 1962); therefore there is no functional inactivation of the adrenal medulla. Indeed, reserpine causes an increased adrenaline excretion which is reduced by the administration of mecamylamine.…”
Section: Action Of Reserpine and Dexamphetamine On The Urinary Catechmentioning
confidence: 74%
“…It was reported that noradrenaline is selectively depleted from adrenal glands of mouse (ERANKO and Hopsu, 1958) and cat (STJARNE and SCHAPIRO, 1959) but this does not occur in rats (COUPLAND, 1958;CALLINGHAM and MANN, 1962). The rate of depletion of adrenal stores is slower than that of amine stores in brain or other peripheral tissues (CALLINGHAM and MANN, 1962), and higher doses of reserpine are required (CARLSSON et aI., 1957 a;LEE, 1967). The relative insensitivity of the adrenal medulla to depletion arises from the slower turn-over rate of medullary amines than of amines in other tissues.…”
Section: Adrenal Medullary Aminesmentioning
confidence: 91%
“…During repletion, there is a considerable overshoot of the noradrenaline content (250% of control) after 7 days followed by a return to the control value in 21 days (CALLINGHAM and MANN, 1962). The ability of adrenal storage granules to accumulate labelled catecholamine returns after reserpine treatment well before the normal levels are restored (LUNDBORG, 1963).…”
Section: F Recovery Of Amine Stores After Reserpine Treatmentmentioning
confidence: 93%
See 2 more Smart Citations